Hubungan Antara Anemia Dan Konsumsi Energi Dengan Kesegaran Jasmani Remaja Putri Di Sma Negeri I Kupang - Pay, M E; Aspatria, Utma; Jutomo, Lewi (Pergizi Pangan DPD NTT, 2009)
Anemia is a condition where iron that brought oxygen, proteins, and hemoglobin in red blood cells that used to burn oxygen to produce energy was decreased. Women adolescents that familiar with anemia possibly will decrease her physical fitness. The objectives of the study were to analyze the relation between anemia, energy intake, and physical fitness among adolescent women. The study was an analytical descriptive study using a cross-sectional study, which is located in SMA Negeri I Kupang. The population was 866 respondents, and samples that taken were 51 persons, using simple random sampling method. The data was collected by using a questionnaire using Sahli method for anemia, Recall data for energy intake, and Harvard step-up test for physical fitness. The result showed that most of the respondents (70,6%) non-anemia, 54,9% of respondents were in well-nourished, and 39,2% had high physical fitness condition. There was a significant relation between anemia (p=0,002) and energy intake (p=0,044) with physical fitness. Suggestions toward (1) health care workers, to be more active in communications, information, and educations, particularly in giving information about anemia and its consequences, (2) adolescent women to maintain their health by consuming healthy and nutrition foods and do exercises continuously.